1993
DOI: 10.1021/bi00071a004
|View full text |Cite
|
Sign up to set email alerts
|

The Leptomonas collosoma spliced leader RNA can switch between two alternate structural forms

Abstract: We have used a combination of physical and molecular biological techniques to examine the structure of Leptomonas collosoma spliced leader RNA. We confirm the general features of the previously proposed structure for the 3' half of the RNA, in which a single-stranded region is flanked by two stem loops. However, we find that the 5' half of the RNA, which contains the splice site, has two competing secondary structures which differ only slightly in stability and which can interconvert on a fast (<1 s) time scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 28 publications
2
64
0
Order By: Relevance
“…1A), is consistent (11). This structure has been confirmed by physical-chemical and enzymatic studies (29,44) and examined by mutagenesis (47). An equivalent structure is also conserved in the nematode SL RNAs (11,53).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…1A), is consistent (11). This structure has been confirmed by physical-chemical and enzymatic studies (29,44) and examined by mutagenesis (47). An equivalent structure is also conserved in the nematode SL RNAs (11,53).…”
mentioning
confidence: 54%
“…Secondary structure of the L. tarentolae SL RNA and linker-scanning mutations in the intron. (A) Secondary structure of L. tarentolae SL RNA, based on the L. collosoma structure (form II) that predominates in vivo (29,44); numbering is relative to the start of transcription. The stem-loop structures are labeled I, II, and III, and the exon-intron junction is indicated by the arrow after nt 39.…”
Section: Methodsmentioning
confidence: 99%
“…During the trans-splicing reaction in trypanosomes and nematodes, spliced leader (SL) RNAs deliver their 5' end as a 5' exon to an independent transcript. The SL RNAs are assembled into ribonucleoprotein particles and have been proposed to adopt secondary structures that bury the 5' splice site in an intramolecular helix (9,36), resembling the interaction of the Ul snRNP with a 5' splice site. Indeed, replacing the 5' splice site region of an adenovirus pre-mRNA with SL RNA sequences from the nematode Caenorhabditis elegans or the trypanosomatid Leptomonas collosoma (C/Adeno or L/Adeno, respectively) allows efficient splicing in HeLa nuclear extract even after the 5' end of Ul is ablated by RNase H in the presence of a DNA oligonucleotide (8).…”
mentioning
confidence: 99%
“…In the mid 1990s, researchers have shown that SL from Leptomonas collosoma and T. brucei displayed two main structures (LeCuyer and Crothers 1993). Similar work in vivo (permeabilized cells) demonstrated that the SL alternates between these structures with predominance of structure 1 (Harris et al 1995).…”
Section: Introductionmentioning
confidence: 97%